Improved Ternary Gray-Code Phase Unwrapping Algorithm for 3D Measurement Using a Binary Defocusing Technique - Yang, Xu; Lin, Houxing; Luo, Jie; Chen, Lei; Lei, Yu (Electronics (Basel), 2021)
By using one-bit binary patterns instead of eight-bit sinusoidal ones, the binary defocusing techniques have been widely applied for high-speed 3D shape measurement. As projector defocusing is required, the phase unwrapping process of these techniques remains challenging. A recently proposed ternary Gray-code method can effectively increase the measurement speed by reducing the number of acquired coding patterns. However, it still has limitations, including the measuring range and a noise problem. To improve these, a new ternary Gray-code method is proposed by utilizing 2D modulation instead of the 1D modulation used in the conventional method. Simulations were conducted to compare these two methods, and the results verify that the proposed method reduces the variance in the introduced intermediate gray value by nearly 90%. Experiments were also carried out with the results verifying the superiority of the proposed method.